Efficacy and safety of single-agent pan-human epidermal growth factor receptor (HER) inhibitor dacomitinib in locally advanced unresectable or metastatic skin squamous cell cancer. (July 2018) - Cavalieri, S.; Perrone, F.; Miceli, R.; Ascierto, P.A.; Locati, L.D.; Bergamini, C.; Granata, R.; Alfieri, S.; Resteghini, C.; Galbiati, D.; Busico, A.; Paielli, N.; et al.
Abstract: Background: In recurrent or metastatic (R/M) skin squamous cell cancer (sSCC) not amenable to radiotherapy (RT) or surgery, chemotherapy (CT) has a palliative intent and limited clinical responses. The role of oral pan-HER inhibitor dacomitinib in this setting was investigated within a clinical trial. Methods: Patients with diagnosis of R/M sSCC were treated. Dacomitinib was started at a dose of 30 mg daily (QD) for 15 d, followed by 45 mg QD. Primary end-point was response rate (RR). Tumour samples were analysed through next-generation sequencing using a custom panel targeting 36 genes associated with sSCC. Results: Forty-two patients (33 men; median age 77 years) were treated. Most (86%) received previous treatments consisting in surgery (86%), RT (50%) and CT (14%). RR was 28% (2% complete response; 26% partial response), disease control rate was 86%. Median progression-free survival and overall survival were 6 and 11 months, respectively. Most patients (93%) experienced at least one adverse event (AE): diarrhoea, skin rash (71% each), fatigue (36%) and mucositis (31%); AEs grade 3–4 occurred in 36% of pts. In 16% of cases, treatment was discontinued because of drug-related toxicity. TP53, NOTCH1/2, KMT2C/D, FAT1 and HER4 were the most frequently mutated genes. BRAF, NRAS and HRAS mutations were more frequent in non-responders, and KMT2C and CASP8 mutations were restricted to this subgroup. Conclusions: In sSCC, dacomitinib showed activity similar to what was observed with anti–epidermal growth factor receptor agents, and durable clinical benefit was observed. Safety profile was comparable to previous experiences in other cancers. Molecular pt selection could improve therapeutic ratio. Highlights: Dacomitinib obtained a 28% response rate in recurrent metastatic skin squamous cell cancer. Safety profile of dacomitinib is similar to other epidermal growth factor receptor inhibitors. BRAF / NRAS / HRAS mutations can be possible markers to ameliorate patient selection.